Intertextuality and microfiction: resources and limits: process and limits (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This article analyzes the concept of intertextuality, with particular interest in the need for limitations to the view that intertextuality is a characteristic of fast fiction. A series of definitions and statements about this resource are listed in short genres. Subsequently, a system of analysis of intertextuality forms used as text construction resources is exemplified. The conclusions focus on the implications of frequent use of these resources in the reading process.
Keywords: microfiction; intertextuality; resources; limits; reading; microfiction; intertextuality; resources; limits; reading